Application of MultiStem® Allogeneic Cells for Immunomodulatory Therapy: Clinical Progress and Pre-Clinical Challenges in Prophylaxis for Graft Versus Host Disease - Vaes, Bart (Frontiers Media S.A., 2012)
The last decade has seen much progress in adjunctive cell therapy for immune disorders. Both corporate and institutional Phase III studies have been run using mesenchymal stromal cells (MSC) for treatment of Graft versus Host Disease (GvHD), and product approval has been achieved for treatment of pediatric GvHD in Canada and New Zealand (Prochymal®; Osiris Therapeutics). This effectiveness has prompted the prophylactic use of adherent stem cells at the time of allogeneic hematopoietic stem cell transplantation (HSCT) to prevent occurrence of GvHD and possibly provide stromal support for hematopoietic recovery. The MultiStem® product is an adult adherent stem cell product derived from bone marrow which has significant clinical exposure. MultiStem cells are currently in phase II clinical studies for treatment of ischemic stroke and ulcerative colitis, with Phase I studies completed in acute myocardial infarction and for GvHD prophylaxis in allogeneic HSCT, demonstrating that MultiStem administration was well tolerated while the incidence and severity of GvHD was reduced. In advancing this clinical approach, it is important to recognize that alternate models exist based on clinical manufacturing strategies. Corporate sponsors exploit the universal donor properties of adherent stem cells and manufacture at large scale, with many products obtained from one or limited donors and used across many patients. In Europe, institutional sponsors often produce allogeneic product in a patient designated context. For this approach, disposable bioreactors producing <10 products/donor in a closed system manner are very well suited. In this review, the use of adherent stem cells for GvHD prophylaxis is summarized and the suitability of disposable bioreactors for MultiStem production is presented, with an emphasis on quality control parameters, which are critical with a multiple donor approach for manufacturing.